Coagulopathy is not predictive of bleeding in patients with acute decompensation of cirrhosis and acute‐on‐chronic liver failure. (16th July 2021) - Campello, Elena; Zanetto, Alberto; Bulato, Cristiana; Maggiolo, Sara; Spiezia, Luca; Russo, Francesco Paolo; Gavasso, Sabrina; Mazzeo, Pierluigi; Tormene, Daniela; Burra, Patrizia; Angeli, Paolo; Senzolo, Marco; et al.
Abstract: Background & Aims: Understanding factors responsible for the increased bleeding tendency in acute‐on‐chronic liver failure (ACLF) would improve the management of these complications. We investigated coagulation alterations in ACLF and assessed whether they were predictive of bleeding. Methods: Cirrhosis patients with ACLF (cases) and acute decompensation (AD, controls) were prospectively recruited and underwent an extensive haemostatic assessment including standard tests, pro and anticoagulant factors, thrombomodulin‐modified thrombin generation (TG) and thromboelastometry (ROTEM ® ). In study part 1 (case‐control), we compared coagulation in ACLF vs AD. In study part 2 (prospective), all patients were followed for bleeding, and predictors of outcome were assessed. Results: Ninety‐one patients were included (51 with ACLF, 40 with AD). Infections and ascites/renal dysfunction were the most common precipitating and decompensating events. Platelet count was lower while INR and activated partial thrombin time were longer in ACLF cohort vs AD. Regarding clotting factors, fibrinogen and factor VIII were comparable between groups while protein C and antithrombin were significantly reduced in ACLF. Endogenous thrombin potential by TG was comparable between groups. Clotting formation time and clot stability by ROTEM ® were significantly lower in ACLF, indicative of a more hypocoagulable state. No haemostasis alteration could discriminate between patients who had bleeding complications during hospitalization and those who did not. Conclusion: We found coagulation changes in ACLF to largely overlap with that of AD and evidence of preserved coagulation capacity in both groups. ROTEM alterations were indicative of a more pronounced hypocoagulable state in ACLF; however, no correlation was found between such alterations and bleeding.